A survey of the bat fauna in the vicinity of Turjak (South Central Slovenia) - Presetnik, Primož (Založba Univerze v Ljubljani / University of Ljubljana Press, 2001)
Results of the survey carried out in the vicinity of Turjak (Dolenjska, Slovenia) between July 1999 and January 2001 are presented in the article. At least fifteen species were recorded with the monitoring of potential roost sites, mist netting and the use of heterodyning bat detectors. Pipistrellus pipistrellus was most commonly observed species. Species not frequently found in Slovenia - Rhinolophus euryale, Myotis natterreri, Myotis emarginatus, Pipistrellus pygmaeus and Nyctalus leisleri - were also detected. Findings of Rhinolophus hipposideros nursery roosts are of particular conservation concern. V članku so predstavljeni rezultati popisa netopirjev, napravljenega v okolici Turjaka med julijem 1999 in januarjem 2001. S pregledi prebivališč, lova z mrežo in predvsem z ultrazvočnim detektorjem je bilo na raziskovanem območju odkritih najmanj 15 netopirskih vrst. Najpogosteje zaznana vrsta je bila Pipistrellus pipistrellus , odkrite pa so bile v Sloveniji redko opažene vrste - Rhinolophus euryale, Myotis natterreri, Myotis emarginatus, Pipistrellus pygmaeus in Nyctalus leisleri. Varstveno so pomembne najdbe porodniških kolonij vrste Rhinolophus hipposideros.